Willingness to use and distribute HIV self-testing kits among people who inject drugs in the San Diego-Tijuana border region - Heather A. Pines; William H. Eger; Britt Skaathun; Carlos F. Vera; Alicia Harvey-Vera; Gudelia Rangel; Steffanie A. Strathdee; Angela R. Bazzi (BMC, 2024)
Abstract Background HIV self-testing (HIVST) could increase HIV testing access among people who inject drugs (PWID), and secondary distribution (i.e., peer-delivery) of HIVST kits in PWID social networks could further expand coverage. We assessed willingness to use and distribute HIVST kits among PWID in the San Diego-Tijuana border region. Methods From 2020 to 2021, HIV-negative PWID in San Diego, USA, and Tijuana, Mexico, completed surveys and provided data on individual (N = 539) and social network (N = 366) characteristics. We used modified Poisson regression to examine the effects of individual and social network characteristics on willingness to use and distribute HIVST kits. Results Most participants were willing to use (81%) and distribute (81%) HIVST kits. At the individual level, prior HIV testing was positively associated with willingness to use (adjusted prevalence ratio [aPR] = 1.24, 95% confidence interval [CI] 1.10-1.40) and distribute (aPR = 1.27, 95% CI 1.12-1.43) HIVST kits, while perceiving oneself to be at higher HIV risk than others was negatively associated with willingness to use HIVST kits (aPR = 0.83, 95% CI 0.74-0.93). At the network level, willingness to distribute HIVST kits was positively associated with network size (aPR = 1.04 per member, 95% CI 1.01-1.08) and greater proportions of one's network encouraging them to use drugs (aPR = 1.29, 95% CI 1.16-1.44) and having a history of homelessness (aPR = 1.51, 95% CI 1.31-1.74) or detention/arrest (aPR = 1.57, 95% CI 1.36-1.82), and negatively associated with a greater proportion of one's network including "very close" persons (aPR = 0.80, 95% CI 0.69-0.94). Conclusions We found high potential for HIVST kits and their secondary distribution to increase HIV testing among PWID who face the greatest barriers to facility-based testing.